SCHOOL SAFETY STUDY ON 11 DIFFERENT SCHOOLS IN ISTANBUL - Tufan ADIGÜZEL; Elmas ALVER; Osman ÖZTÜRK (International Journal of Eurasia Social Sciences, 2016)
One of pre-conditions that to maintain educational activities is to provide school security and to prevent violence in schools to feel safe students. The purpose of safe school is to determine students’ perception towards schools and to state the factors which can influence the perception of students. In this study, school climates of 11 schools specified by the protocol that signed with Ministry Education of Turkey (MEB) were empirically conducted as a part of CSG-BAU Safe School Project. Target population of this study was 5th – 12th grades students and their teachers in public schools in Istanbul. Participants were 2437 students and 261 teachers from 11 public schools conveniently selected from the districts of Istanbul. Şirin (2010) instrument which have four subdomains (academic expectation, academic interest, communication, and respect and safety) was used in this study. Descriptive statistics, MANOVA, and Pearson correlation were conducted when analyzing the perception of the school climate with respect to teacher, student, district and grade. The results showed that the teachers’ and students’ school climate perceptions were positive, but the school climate perceptions of teachers and students with respect to districts and grades were statistically significant in some subdomains of the instruments. Correlation of school climate perception between teachers and students was weak, but significant because of sample size.